Chromosome counts and karyotype analysis of some representatives of genus Cirsium Mill. (Asteraceae) in Turkey - Polat, Nevra; Kiran, Yasar; Sahin, Ahmet; Yildiz, Bayram; Arabaci, Turan (Firenze Univ Press, 2018)
The chromosome number and karyotype analysis of nine species (10 taxa) of genus Cirsium Mill. distributed in Turkey were analyzed. The somatic chromosome number of Cirsium sipyleum O. Schwarz, C. candelabrum Griseb., C. creticum d'Urv. subsp. creticum, C. elodes M. Bieb., C. subinerme Fisch. & C. A. Mey., C leucopsis DC., C libanoticum DC. subsp. arachnoideum P. H. Davis & Parris and C. arvense (L.) Scop. were determined as 2n=2x=34. Cirsium pubigerum DC. var. caniforme Petr. and var. paphlagonicum Petr. showed 2n=4x=68 chromosome numbers. The chromosomes of the examined taxa predominantly have median region (m) and rarely median point (M) and submedian region (sm) karyotypes. The chromosome number and morphology of Cirsium sipyleum, C. pubigerum var. paphlagonicum, C. leucopsis and C libanoticum subsp. arachnoideum are newly reported in the present study.
Keywords: Cardueae; chromosome number; karyotypes; new count; Turkey